CLINICAL COURSE AND APPROACHES TO TREATMENT OF CONGENITAL COMPLETE ATRIOVENTRICULAR BLOCK IN CHILDREN - Shadieva Khalima Nuridinovna; Xolikova Gulnoz Asatovna (American Journals Publishing, 2024)
A description of the clinical picture of several patients with congenital complete atrioventricular block (CCAVB) is given: isolated conduction disturbance in 1 patient and in 3 children a combination of CCAVB with congenital heart defects such as ASD, PDA. One girl with congenital heart disease (ASD) was diagnosed with Frederick's syndrome. Characteristic complaints, objective changes, as well as signs of retarded physical development were identified. All children underwent implantation of a single-chamber cardiac pacemaker. Along with pacemaker implantation, surgical correction of congenital heart disease was performed. After the treatment, there was a positive trend in the condition of the patients, normalization of physical development indicators, restoration of ECG and EchoCG parameters.
Keywords: Childrenn, complete atrioventricular block, congenital heart disease, ASD, PDA.